If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -4x = 2x + -62 Reorder the terms: -2 + -4x = -62 + 2x Solving -2 + -4x = -62 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + -4x + -2x = -62 + 2x + -2x Combine like terms: -4x + -2x = -6x -2 + -6x = -62 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + -6x = -62 + 0 -2 + -6x = -62 Add '2' to each side of the equation. -2 + 2 + -6x = -62 + 2 Combine like terms: -2 + 2 = 0 0 + -6x = -62 + 2 -6x = -62 + 2 Combine like terms: -62 + 2 = -60 -6x = -60 Divide each side by '-6'. x = 10 Simplifying x = 10
| 5(x-20)+3=7x+9 | | -3-6x+3x^2=0 | | 59x-20+3=7x+9 | | 1=t-0.006 | | C-8.9=4.6 | | 2+5y=12 | | T+2.7=3.3 | | 7x+9=-5x-111 | | R-80=160 | | 5x-8=3x-22 | | 3x+56*89:2*45-576+123= | | (7+9i)+(10+4i)= | | 1=4+3y | | -4-4x=-6x+2 | | 3x-6=76 | | 1-x=-11-3x | | 2+1=4 | | -8+12b=13b | | -4-5p=10-3p | | -t+6+8t=9t-4 | | 2sin^2x-3cosx-3=0 | | m+9=-4 | | 5-x^2-2x=-3 | | 9-2x+2=5x+4 | | 8s=-4+6s | | 8k-1=9k-7 | | 9h=8+10h | | 2x^3-9x^2+13x-6=0 | | -8+4f=-1+5f | | 23-7k=-6k | | 7r=8r-8 | | 3a+5=2a-5/4 |